(untitled) (International Journal of Plant Biology, 2015)
Olive cultivation in hot arid areas is hindered by the scarcity of irrigation water. The exploitation of saline water has been proposed as a solution to partially cover plant water demands. This paper presents the effects of salinity [0, 60 and 120 mM sodium chloride (NaCl)] on physiological and reproductive functions of cultivars Koroneiki and Amphissis in a closed hydroponic system. Shoot growth was markedly reduced in high salinity dose in Amphissis (−81%) and Koroneiki (−75%). The photosynthetic rate was significantly reduced at 120 mM NaCl for both cultivars, as well as chlorophyll and carotenoids content (43% and 44%, respectively). The Na+ content in all plant parts increased in both salinity doses especially in Amphissis while K concentration decreased for both cultivars. Inflorescences in Amphissis were severely damaged due to salinity. Consequently, pollen sampling and in vitro germination study was only feasible for Koroneiki. Indeed, Koroneiki pollen germination was reduced at 60 mM NaCl (−42%) and at 120 mM NaCl (−88%). Pollen tube length was also reduced by 15% and 28% for the middle and high salinity dose, respectively. The results of the present study indicate that Amphissis is more sensitive in high salinity doses compared to Koroneiki and that reproductive functions are severely affected by salinity.